The effect of dose calculation algorithms on the normal tissue complication probability values of thoracic cancer - Ahmad, Noor Ashikin (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2015)
Purpose: To identify the effect of dose calculation algorithms on the Normal Tissue Complication Probability values of thoracic cancer. Materials and Methods: NTCP values from BIOPLAN software is calculated based on standard DVH data. Dose distributions of treatment plans are calculated by using two different algorithms of Oncentra Masterplan (OMP) treatment planning system (TPS) which are Collapse Cone and Pencil Beam. Four treatment plans are created and DVHs are evaluated based on criteria of acceptance level. NTCP values for thorax plan one and two are evaluated by using different algorithm. Results: The coverage of the target volume for all treatment plans has achieved the desired isodose for at least 90% of isodose at 1 00% of volume. Collapsed cone shows better calculation in three beam but pencil beam is better in 5 beams calculation. The NTCP values of the LKB model are slightly higher than RS model for both cases even though using different kind of algorithm. Conclusions: There is no difference between pencil beam and collapsed cone algorithms in term of NTCP values. NTCP values are due to physical and biological effects. Mathematically, both treatment plans have higher probability to develop the complication but the numbers in this paper are not wholly based on clinical or even experimental data. It may due to patient-related factors, patient history or the modalities used in treatment delivery.